Investigation of effects of metformin on rats’ urinary bladder contractions (Annals of Medical Research, 2022)
Aim: The effects of different doses of metformin on the contractility of female Sprague-Dawley rat bladder strips were evaluated.Materials and Methods: Rats were decapitated and the bladder strips measuring 2–4 × 6–12 mm prepared from the whole urinary bladder were suspended in isolated tissue organ baths. Tissues in the chambers were rinsed every 30 minutes for 60 minutes and allowed to equilibrate. Afterwards, 10-4 M acetylcholine was added to all isolated tissue baths. After one hour of rinsing, metformin (2 mM) was added and incubated 30 minutes. After 30 minutes, the same dose of acetylcholine was added without rinsing, and immediately after this protocol was performed with 10 mM and 20 mM metformin doses.Results: All of these doses led to increased contractions in a dose-dependent manner. The 2 mM dose did not induce any contraction in area (213.67±33.10 %) compared to control, but there was a significant increase in peak-to-peak amplitude (127.65±4.24 %, p=0.009). In addition, the peak-to-peak amplitude was significantly increased at the 10 mM and 20 mM doses (163.86±8.57 % and 162.58±6.76 %, p=0.0001, respectively) compared to the control and there was a statistically significant difference. In addition, the area value increased significantly compared to control at the 20 mM dose alone (3767.64±733.70 %, p=0.0001).Conclusion: Our present data show that the treatment of varied high doses of metformin may lead to the increase of contractions at ex vivo isolated tissue bath. Therefore, this effect can escalate some symptoms of diabetic bladder dysfunction.
Keywords: Metformin; Contraction; Isolated tissue bath; Urinary bladder; Diabetic bladder dysfunction